Cryptography and network security - Bose, S.; Vijayakumar, P. (Always learning., 2016)
This book elaborates the basic and advanced concepts of cryptography and network security issues. It is user friendly since each chapter is modelled with several case studies and illustration. All algorithms are explained with various algebraic structures to map the theoretical concepts of cryptography with modern algebra. Moreover, all the concepts are explained with the secure multicast communication scenarios that deal with one to many secure communications.